Population and distribution pattern of Poropuntius tawarensis in Lake Laut Tawar, Central Aceh Regency - Mufti Aulia Rahman; Abdullah Abdullah; Safrida Safrida; Muhammad Ali Sarong; Haekal Azief Haridhi (Depik, 2024)
Poropuntius tawarensis is an endemic fish of Laut Tawar that is currently classified as Endangered according to the IUCN Red List. The decline in its population is caused by habitat degradation, overfishing, and the introduction of alien species that act as predators This study aims to analyze the diversity and distribution patterns the population of kawan fish (Poropuntius tawarensis) in Lake Laut Tawar, Central Aceh Regency. Fish samples were collected from four different locations and analyzed using the Shannon-Wiener and Morisita indices. The results indicate that the diversity level of kawan fish (Poropuntius tawarensis) is classified as a "Low level of diversity," with significant differences between sampling locations. All locations (Hakim Balai Bujang: 0.796845; Toweren: 0.301815; Kelitu: 0.753952; Kala Segi: 0.467728) show a low level of diversity, which is H' 1. Analysis using the Standardized Morisita Index indicates that the distribution pattern of kawan fish (Poropuntius tawarensis) in the four study locations tends to be clumped dispersion. This is evidenced by Morisita index values greater than 1 at all sites (Hakim Balai Bujang: 1.2834; Toweren: 1.0212; Kelitu: 1.0053; Kala Segi: 1.0134). These values suggest that the fish tend to concentrate in specific areas within each village rather than being evenly distributed.Keywords:Poropuntius tawarensisLaut Tawar LakeDiversityDistribution Patterns